Seasonal changes in certain blood antioxidants in cattle and buffaloes - YATOO, MOH IQBAL; DIMRI, UMESH; SHARMA, MAHESH CHANDRA (The Indian Journal of Animal Sciences, 2014)
The aim of this study was to find out the impact of climate change and production stress on oxidative stress indices in lactating and non-lactating cattle and buffalo under tropical conditions. Oxidative stress (OS) indices like catalase (CAT), super oxide dismutase (SOD), glutathione reductase (GSH) and lipid peroxidase (LPO) were estimated from the blood samples during winter, spring and summer. Oxidative stress indices were significantly elevated in both cattle and buffalo during hot summer and cold winter than during spring season indicating stress due to climatic stress. Significantly elevated levels of oxidative stress indices were recorded in lactating animals under different seasons than non-lactating animals indicating production stress in addition to climatic stress in lactating animals. Climate change and demand for heavy milk production predisposes animals to oxidative stress. Strategies to combat climate change induced oxidative stress need to be devised to prevent animal sufferings and production loss.